(3GdeUGHjM GdSfjI aj WH GdHQjIs - (3GdbdjhHj , CMeO Hf CMeO Hf SdGeI GdbddjhHj, TgGH GdOjf CHh GdYHGS,J (B1069 (3g` s ((3eUWai Hf eMeO GdHSfhi s)
(3ChdgG (B:s
(3agPG eDda dWja jLgdg EfSGf , hdG jMJGL ai eYQaJg Edi CYhGf , bO LeY eG JaQb ai ZjQg ef GdJUGfja , hCZfi Yf eQGLYI eG ShGg ef GdJCdja s
(3BNQgG (B:s
(3TQH GdNeQ jhQK NddG ai LhgQ GdYbd hehJ GdaLGAI hjaJM cd TF hjhLH SNW GdQH , hjfSi GdTgGOIYfO GdehJ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B76s
(3GfXQg eY GdfMaI GdLGeYI Qbe (B" 366"s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B92 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B148s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B490 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B233 s
Keywords: (3GdWHs